Improvement of the existing technology of cadastral assessment of irrigated crop land in case of Uzbekistan - Babajanov A.; Roziboev S.; Inamov B. (E3S Web of Conferences)
The article examines and analyses the existing methods of cadastral assessment of irrigated agricultural lands, especially the existing methods for comparative assessment of the quality of irrigated lands, specific proposals and recommendations for further improvement of this methodology on the basis of adaptation to today’s limited water distribution conditions; specific proposals and recommendations for further improvement of this methodology on the basis of adaptation to today’s limited water distribution conditions; specific proposals for the simplification and simplification of the methodology for determining the normative value of land, which is carried out annually in the country, using the data of soil assessment, have been developed and are comprehensively substantiated.